Airborne culturable fungi in naturally ventilated primary school environments in a subtropical climate. (April 2015) - Salonen, Heidi; Duchaine, Caroline; Mazaheri, Mandana; Clifford, Sam; Morawska, Lidia
Abstract: There is currently a lack of reference values for indoor air fungal concentrations to allow for the interpretation of measurement results in subtropical school settings. Analysis of the results of this work established that, in the majority of properly maintained subtropical school buildings, without any major affecting events such as floods or visible mould or moisture contamination, indoor culturable fungi levels were driven by outdoor concentration. The results also allowed us to benchmark the "baseline range" concentrations for total culturable fungi, Penicillium spp., Cladosporium spp. and Aspergillus spp. in such school settings. The measured concentration of total culturable fungi and three individual fungal genera were estimated using Bayesian hierarchical modelling. Pooling of these estimates provided a predictive distribution for concentrations at an unobserved school. The results indicated that "baseline" indoor concentration levels for indoor total fungi, Penicillium spp., Cladosporium spp. and Aspergillus spp. in such school settings were generally ≤1450, ≤680, ≤480 and ≤90 cfu/m 3, respectively, and elevated levels would indicate mould damage in building structures. The indoor/outdoor ratio for most classrooms had 95% credible intervals containing 1, indicating that fungi concentrations are generally the same indoors and outdoors at each school. Bayesian fixed effects regression modelling showed that increasing both temperature and humidity resulted in higher levels of fungi concentration. Graphical abstract: Highlights: 25 naturally ventilated school settings in a subtropical climate were investigated. Indoor culturable fungi were mainly driven by outdoor concentration. The concentration of culturable fungi is generally ≤1450 cfu/m 3 and I/O-ratio ≤2. Elevated levels indicate the presence of abnormal microbe sources indoors. The study guide future determination of criteria for assessing culturable fungi in a subtropical area.